The Approbation of a Mathematical Model of the Influence of Three-Level Semantic Representation of an Educational Mes-sage on the Dynamics of Students’ Creativity - Gafarova, Yelena; Belevitin, Vladimir; Korchemkina, Yuliya; Smyrnov, Yevgen; Khasanova, Marina (International Journal of Engineering and Technology, 2018)
The article presents the description and approbation experience of a mathematical model of three-level semantic representation of training signals. The results of approbation indicate a significant impact of the ternary nature of training signals on the dynamics of the changes in the verbal creativity indicator.Â Â Â